Exploratory study on reflective writers: the case of personal blogs / Wan Najmiyyah Wan Md Adnan - Wan Md Adnan, Wan Najmiyyah (2009)
Blogging has been established as a potential source for reflection. Previous researches done on the relationship between blogging and reflective writing focused more on classroom blogs monitored by the teachers. Studies on the relationship between personal blogs and reflective writing are still relatively scarce, especially in Malaysian context. Thus, the present exploratory study investigated on the bloggers’ perception of blogging and looked into how personal blogs affect students’ abilities to become reflective writer. The study also explored the strengths of blogging in developing reflective writers. Two types of instruments namely document analysis and semi-structured interview were used on three respondents selected through nonpurposive random sampling. The conceptual framework for the present study was conceptualized based on previous researches done on the relationship between blogs and reflective learning mainly from Scaletta (2006) and Quinn et. al (2007). Bereiter and Scardamalia (1987)’s characteristics of mature writers and knowledge transforming model, Flower and Hayes (1983)’s and Graham and Harris (1989)’s novice vs. expert writer characteristics were used to extract the themes for the findings of the study. The findings indicated that bloggers viewed blogging as a place for self-reflection and their interests in writing contributed to the reasons why they started blogging in the first place. The data analysis from the respondents’ personal blogs also conformed to the fact that the respondents featured the characteristics of reflective writers when writing their blog entries. From the previous two findings, the researcher managed to identify the strengths of personal blogs in developing reflective writers. In conclusion, despite the informal and interpersonal nature of personal blogs, this study provided evidence that personal blogs also contributed to the development of reflective writers.